Women’s economic empowerment, participation in decision-making and exposure to violence as risk indicators for early childhood caries - Morenike Oluwatoyin Folayan (BMC Oral Health, 2020)
Abstract Objectives In view of the association between early childhood caries (ECC])and maternal social risk factors, this study tried to determine if there were associations between indicators of processes, outputs and outcomes of women’s empowerment, and the prevalence of ECC. Methods In this ecological study, indicators measuring the explanatory variables - economic empowerment, decision-making and violence against women - were selected from the Integrated Results and Resources Framework of the UN-Women Strategic Plan 2018–2021 and WHO database. Indicators measuring the outcome variables - the prevalence of ECC for children aged 0 to 2 years, and 3 to 5 years - were extracted from a published literature. The general linear models used to determine the association between the outcome and explanatory variables were adjusted for economic level of countries. Regression estimates (B), 95% confidence intervals and partial eta squared (η2) were calculated. Results Countries with more females living under 50% of median income had higher prevalence of ECC for 3 to 5-year olds (B = 1.82, 95% CI = 0.12, 3.52). Countries with higher percentage of women participating in their own health care decisions had higher prevalence of ECC for 0 to 2-year-olds (B = 0.85, 95% CI = 0.03, 1.67). Countries with higher percentage of women participating in decisions related to visiting family, relatives and friends had higher prevalence of ECC for 3 to 5-year-olds (B = 0.67, 95% CI = 0.03, 1.32). None of the indicators for violence against women was significantly associated with the prevalence of ECC. Conclusion Empowerment of women is a welcome social development that may have some negative impact on children’s oral health. Changes in policies and norms are needed to protect children’s oral health while empowering women.